Hydrogen-, halogen-, and chalcogen-bond driven solid-state assembly of functional supramolecular systems - De Silva, Simanhewa Lakshitha Viraj (Kansas State University, 2023)
The chalcogen bond (ChB) is relatively underexplored in the context of controlling supramolecular self-assembly. In order to improve our understanding of the structural influence and tunability of the ChB, a series of alkylselenoacetylene derivatives were devised, synthesized and characterized using multinuclear NMR and single crystal X-Ray diffraction (SC-XRD), Chapter 2. Density functional theory (DFT) calculations showed excellent tunability and correlation between the magnitude of the [sigma]-hole potential and the interaction energies of the synthesized compounds. Molecular electrostatic potential maps (MEPs) accurately predicted the plausible synthon assembly and the directionality of the ChBs based on the donor-acceptor preference. To further enhance control over the magnitudes on both [sigma]-holes on bivalent chalcogen atoms, a series of ‘triply activated’ phenylchalcogenacetylene derivatives were synthesized, Chapter 3. The [sigma]-hole potential and the ChB donor ability were ranked based on the MEPs and the structural outcomes were postulated. The ChB preference of the synthons were established using crystallography, and the resulting geometrical features were benchmarked against the reported literature examples extracted from the Cambridge Structural Database (CSD). Cell viability assays for the synthesized target compounds against HeLa cell lines showed that the atom-to-atom substitution of selenium with tellurium can significantly improve the chemotherapeutic properties of these compounds by an order of magnitude. The structural influence of hydrogen, halogen, and chalcogen bonding was explored based on three series of 1,3,4-chalcogenadiazole derivatives in Chapter 4. The delicate balance between the intermolecular interactions present were clearly displayed in the two polymorphs of 5-(4-iodophenyl)-1,3,4-thiadiazol-2-amine (T1-S-I). The MEPs showed the influence of atom-to-atom substitution on the [sigma]-hole potentials, where substitution of S with Se led to bifurcated ChBs and activated halogens resulted in 100% probability of halogen bond (XB) expectation. MEPs also succeeded in predicting the preferred hydrogen bond (HB) synthon in the crystal structures of the 1,3,4-chalcogenadiazole derivatives. In Chapter 5, we examined (i) the influence of hydrogen, halogen, and chalcogen-bond donors on cocrystal synthesis; (ii) the possibility of predicting whether salts or cocrystals would form in a series of 2-amino-1,3,4-chalcogenadiazole derivatives. Four 1,3,4-chalcogeadiazole derivatives were screened for co-crystallization with 38 carboxylic acid coformers with a 82% success rate. A total of 17 crystal structures were obtained, with 71% resulting in salts and 29% leading to cocrystals. The predictability of salt and cocrystal synthesis was explored based on FT-IR, [delta]pKa, [delta]D[subscript C-O] which showed that FT-IR and [delta]D[subscript C-O] worked best with these systems. We also demonstrated the usefulness of DFT calculations for predicting, a priori, whether a salt or a co-crystal would form. To create a structural competition between XB and ChB we replaced the amino group of 2-amino-5-(4-halophenyl)-1,3,4-chalcogenadiazole with bromo/iodo substituents to obtain a library of five 2-halo-5-(4-halophenyl)-1,3,4-chalcogenadiazole derivatives, Chapter 6. This produced five crystal structures, all were isostructural and contained primarily chalcogen and halogen bonding interactions. Hirshfeld surface analysis and energy framework calculations showed that, collectively, a bifurcated chalcogen bond was stronger than a single halogen bond and thus more structurally influential. The 1,3,4-chalcogenadiazole derivatives that can form all three hydrogen, halogen and chalcogen bonding noncovalent interactions could provide a promising design strategy for creating flexible crystal systems. Considering the novelty of the mechanically flexible systems we decided to explore potential structural modifications of 1,3,4-chalcogadiazoles using amide substituents with varying chain lengths and explore the structure-property relationship in Chapter 7. Fourteen crystal structures were obtained including several polymorphic forms. All the crystals either showed elastic bending or brittleness and none showed plastic deformation. The presence of corrugation and interlocking resulted in elastic bending systems 64% of the time and the lack of corrugation, slip planes, and interlocking results in brittleness in 36% of the crystals. Finally, in Chapter 8, three cavitands functionalized with chalcogen-bond donors on the upper rim were synthesized and characterized. The ¹H and ⁷⁷Se NMR titration experiments demonstrated that host-guest binding was facilitated by chalcogen bonding.
Keywords: Hydrogen bond; Halogen bond; Chalcogen bond; Sigma-hole; Flexible crystals; Crystal engineering